Three dimensional distribution of surfactant in microspheres revealed by synchrotron radiation X-ray microcomputed tomography - Li Wu; Manli Wang; Vikramjeet Singh; Haiyan Li; Zhen Guo; Shuangying Gui; Peter York; Tiqiao Xiao; Xianzhen Yin; Jiwen Zhang (Elsevier, 2017)
This study investigated the formulation mechanism of microspheres via internal surfactant distribution. Eudragit L100 based microspheres loaded with bovine serum albumin were prepared by solid in oil in oil emulsion solvent evaporation method using acetone and liquid paraffin system containing sucrose stearate as a surfactant. The fabricated microspheres were evaluated for encapsulation efficiency, particle size, production yield, and in vitro release characteristics. The internal structures of microspheres were characterized using synchrotron radiation X-ray microcomputed tomography (SR-µCT). The enhanced contrast made the sucrose stearate distinguished from Eudragit to have its three dimensional (3D) distribution. Results indicated that the content and concentration determined the state of sucrose stearate and had significant influences on the release kinetics of protein. The dispersity of sucrose stearate was the primary factor that controlled the structure of the microspheres and further affected the encapsulation efficiency, effective drug loading, as well as in vitro release behavior. In conclusion, the 3D internal distribution of surfactant in microspheres and its effects on protein release behaviors have been revealed for the first time. The highly resolved 3D architecture provides new evidence for the deep understanding of the microsphere formation mechanism.